Evolution of Digitized Societies Through Advanced Technologies - Choudhury, Amitava; Singh, T. P.; Biswas, Arindam; Anand, Mrinal (Advanced Technologies and Societal Change, 2022)
X, 209 p. 32 illus., 25 illus. in color.